Municipal secondary-treated effluent data seem to be a suitable source of information for human viral trends - Elsa T. Rodrigues; Joana M. Oliveira; Anália Carmo; Miguel A. Pardal; Ana M. Matos (Ecotoxicology and Environmental Safety)
Employing a long-time series of municipal wastewater samples collected in 2020, the present study aims to confirm whether the appearance of SARS-CoV-2 influences the environmental load and behaviour of both JC Virus and Norovirus, determine the ability of the selected wastewater treatment plant (WWTP) to remove viral genomes, and assess if secondary-treated effluent data is somehow related to the incidence of the viral diseases reported by the local hospital. From the 11 raw influent and 52 secondary-treated effluent samples tested, JC Virus data present an occurrence frequency of 100 %, showing two different abundance patterns along the year, before and after the appearance of SARS-CoV-2. The constant detection of JC nucleic acids in wastewater reinforces the idea that urine is responsible for transmitting this virus. The Norovirus genogroup (G) II was detected more frequently than GI, both in influents and effluents, and their characteristic incidence peaks were not observed in late 2020. Regarding SARS-CoV-2 RNA, it appeared only in 5.8 % of the effluents, possibly due to the iron dosing used by the WWTP to reduce both phosphorus and organic matter concentrations in order to meet the requirements of European legislation, and/or the pre-filtration laboratory step which neglected the possibility of viral association with the solid fraction. The results suggest a poor performance of the WWTP, since Log removal values below 1.8 were determined. We were able to trace the development of local Norovirus outbreaks in the effluent samples to some extent, suggesting that secondary-treated effluents may be used to monitor human viruses by following viral nucleic acid levels.